STYLISTIC FEATURES OF PHILOSOPHICAL MONOLOGUES IN THE UZBEK TRANSLATION OF DOSTOEVSKY'S NOVEL THE BROTHERS KARAMAZOV (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article discusses the stylistic features of philosophical monologues in the Uzbek translation of the novel by F.M. Dostoevsky "The Brothers Karamazov". The object of this research is the philosophical monologues of the characters, primarily Ivan Karamazov, Elder Zosima and Dmitry Karamazov, containing complex ideological, religious, ethical and existential concepts. The subject of this research is the transformation of stylistic, syntactic, lexical-semantic, intonation-rhythmic features of the original text in the process of translation into Uzbek. The author uses the methods of comparative analysis, stylistic interpretation, contextual and semantic analysis, as well as elements of translation analysis. The features of the transmission of polyphony, internal dialogue, expressive gradation, rhetorical structures and religious-philosophical terminology in the Uzbek translation are revealed. It is concluded that philosophical monologues in the Uzbek version retain the ideological content of the original, but are subject to a certain stylistic adaptation due to the typological features of the Uzbek language and the national-cultural context.